TINJAUAN HUKUM BISNIS TERHADAP PERLINDUNGAN DESAIN INDUSTRI DALAM UNSUR KEBARUAN YANG TELAH TERDAFTAR - Fitriyani Pakpahan, Elvira; O.K. Isnainul; Kesuma Wijaya, Emil (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Industrial Design is a form of legal protection for the external appearance or visual form of a new product, which can be in the form of lines, patterns, colors, or a combination of these elements that give an aesthetic and functional impression to the product. This research discusses the limitations of the element of novelty in canceling registered industrial design rights. Law Number 31 of 2000 concerning Industrial Designs only states that an industrial design is considered new if at the date of application the design is not the same as a previously registered industrial design. The phrase "not the same" in Article 2 paragraph (2) of Law Number 31 of 2000 gives rise to multiple interpretations and creates legal uncertainty regarding the limits of the element of novelty. This research aims to analyze the business law perspective in analyzing potential conflicts or legal disputes related to the protection of registered industrial designs with a focus on the element of novelty. This research uses normative legal methods with a statutory approach and a case approach. The results of the study show that legal protection for industrial designs in Indonesia applies a constitutive system with a First To File registration system, but substantive examination of industrial design registration is only carried out if there are objections to the application. Elements of novelty that are not well understood or deliberately ignored can lead to potential legal disputes between the design owner and other parties who feel their design rights have been violated. Conflicts often arise if there is an allegation that a registered design does not meet the element of novelty or if there is a claim that the design previously existed. These disputes can result in the cancellation of registered industrial design rights.